Formation of philosophy of language (Eurasian Journal of Philology Science and Education, 2018)
This article describes the steps of the formation of a separate branch of philosophy of language – oneof the central areas of research in modern western philosophy, which focuses on understanding of thelanguage as the key to understanding the thinking and knowledge. The forerunners of the philosophicaland linguistic areas were Rousseau with ideas about the origin of writing, John. Mill contribution to thetheory of reference, von Humboldt and others.The transition from the philosophical classics to the periodof the philosophy of language is associated with a change in the object of research: the place of «ideas»come to the linguistic nature – offers and terms.Since the second half of the XX century, all the majorsections of the philosophy of experiencing at least stylistic influence of philosophical and linguistic turnsof thought. Thus, the philosophy of language – it’s not just separately taken the direction of philosophicalstudies, but also a particular style of philosophical thinking, which is associated with a primary interestin the question of how to construct theories and with the study of the principles of orderliness means ofexpressing knowledge.